Grotowski's bridge made of memory : embodied memory, witnessing and transmission in the Grotowski work - Laster, Dominika (Enactments., 2016)
One of Polish theater's great innovators is Jerzy Grotowski, well known for his lifelong research on the work of the self with and through the other. Taking various forms and undergoing multiple transformations, this single underlying proposition propelled Grotowski's career. In Grotowski's Bridge Made of Memory, Dominika Laster analyzes core aspects of Grotowski's work such as body-memory, vigilance, witnessing, verticality, and transmission, arguing that these performance praxes involve a deliberate blurring of the boundaries of the self and other. This comprehensive study traces key thematic threads across all phases of Grotowski's research, examining lesser-known aspects of his praxis such as performance compositions structured around African and Afro-Caribbean traditional songs and ritual movement, as well as textual material from the Christian Gnostic tradition. As an active process of research and questioning conducted through the "body-being" of the performer, the Grotowski work is a practical realization of the often highly theoretical and abstract discussions of one of the field's main preoccupations: embodied practice as a way of knowing.